2018
DOI: 10.1016/j.afjem.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary resuscitation by Emergency Medical Services in South Africa: Barriers to achieving high quality performance

Abstract: IntroductionSurvival rates from out-of-hospital cardiac arrest significantly improve when high-quality cardiopulmonary resuscitation (CPR) is performed. Despite sudden cardiac arrest being a leading cause of death in many parts of the world, no studies have determined the quality of CPR delivery by Emergency Medical Services (EMS) personnel in South Africa. The aim of this study was to determine the quality of CPR provision by EMS staff in a simulated setting.MethodsA descriptive study design was used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Multiple surveys in SSA have demonstrated that even clinicians including physicians do not have adequate basic life support (BLS) and advanced cardiac life support (ACLS) training (about half of those surveyed), and the majority are unable to operate an automated external defibrillator (AED) [13,97,98]. In South Africa where EMS services are available, overall knowledge and skill performance of CPR is still well below standard by EMS personal with only 25% of the required standards met [99]. In addition to lack of optimal resuscitative measures, quality improvement schemes are also deficient in SSA.…”
Section: Cardiopulmonary Resuscitation (Cpr)mentioning
confidence: 99%
“…Multiple surveys in SSA have demonstrated that even clinicians including physicians do not have adequate basic life support (BLS) and advanced cardiac life support (ACLS) training (about half of those surveyed), and the majority are unable to operate an automated external defibrillator (AED) [13,97,98]. In South Africa where EMS services are available, overall knowledge and skill performance of CPR is still well below standard by EMS personal with only 25% of the required standards met [99]. In addition to lack of optimal resuscitative measures, quality improvement schemes are also deficient in SSA.…”
Section: Cardiopulmonary Resuscitation (Cpr)mentioning
confidence: 99%
“…In-hospital survival is relatively higher (22.3-25.5%) than the out-of-hospital setting (10.8%). One of the main reasons for the disparity in survival rate is that rescuers are often performing cardiopulmonary resuscitation (CPR) at sub-optimal standards (5). Therefore, the skill of emergency medical personnel in resuscitation as the first line of assistance is an essential factor in the outcome of cardiac arrest (6).…”
Section: Introductionmentioning
confidence: 99%
“…39 In South Africa, age was one of the demographic factors that influenced the knowledge and skills of cardiopulmonary resuscitation. 41 Jaafar et al 42 reported that females were significantly faster than males in carrying out the chest compressions while participants with less BMI than the study mean were providing more correct chest compressions depth than those with BMI more than the study mean. An earlier Nigerian study showed that while age had statistically significant influence on attitude of some Nigerian students to cardiopulmonary resuscitation, gender did not.…”
Section: Discussionmentioning
confidence: 99%